Influence of Context and Setting on the Mental Health and Wellbeing Outcomes of Ayahuasca Drinkers: Results of a Large International Survey - Perkins, Daniel; Schubert, Violeta; Simonová, Hana; Tófoli, Luís Fernando; Bouso, José Carlos; Horák, Miroslav; Galvão-Coelho, Nicole Leite; Sarris, Jerome (Frontiers in Pharmacology, 2021)
Ayahuasca is a traditional plant decoction containing N,N-dimethyltryptamine (DMT) and various β-carbolines including harmine, harmaline and tetrahydroharmine, which has been used ceremonially by Amazonian Indigenous groups for healing and spiritual purposes. Use of the brew has now spread far beyond its original context of consumption to North America, Europe and Australia in neo-shamanic settings as well as Christian syncretic churches. While these groups have established their own rituals and protocols to guide use, it remains unknown the extent to which the use of traditional or non-traditional practices may affect drinkers’ acute experiences, and longer term wellbeing and mental health outcomes. Hence, this study aimed to provide the first detailed assessment of associations between ceremony/ritual characteristics, additional support practices, and motivations for drinking, and mental health and wellbeing outcomes. The paper uses data from a large cross-sectional study of ayahuasca drinkers in more than 40 countries who had used ayahuasca in various contexts (n=6,877). It captured detailed information about participant demographics, patterns and history of ayahuasca drinking, the setting of consumption, and ritualistic practices employed. Current mental health status was captured via the Kessler 10 psychological distress scale and the mental health component score of the SF-12 Health Questionnaire, while reported change in prior clinically diagnosed anxiety or depression (n=1276) was evaluated using a (PGIC) Patient Global Impression of Change tool. Various intermediate outcomes were also assessed including perceived change in psychological wellbeing, number of personal self-insights attained, and subjective spiritual experience measured via the spirituality dimension of the Persisting Effects Questionnaire (PEQ) and Short Index of Mystical Orientation. Regression models identified a range of significant associations between set and setting variables, and intermediate and final mental health and wellbeing outcomes. A generalized structural equation model (GSEM) was then used to verify relationships and associations between endogenous, mediating and final outcome variables concurrently. The present study sheds new light on the influence of ceremonial practices, additional supports and motivations on the therapeutic effects of ayahuasca for mental health and wellbeing, and ways in which such factors can be optimized in naturalistic settings and clinical studies.